FORMULASI DAN UJI KETAHANAN SEDIAAN PARFUM SPRAY BUNGA LILI ( Lilium longiflorum) - Simorangkir, Delisma Marsauli (Jurnal Penelitian Farmasi Dan Herbal, 2025)
This study aimed to formulate and evaluate the fragrance longevity of lily flower (Lilium longiflorum) spray perfume. Lily essential oil was extracted using steam distillation and formulated at concentrations of 5%, 10%, and 15% with additional fixatives, solvents, solubilizers, and preservatives. Evaluations included organoleptic tests, density, pH, fragrance longevity, stability, and aroma preference. Results showed that all formulations had good clarity, homogeneity, and skin-safe pH values (5.29–5.55). Formula 2 (10%) provided the best balanced fragrance intensity and received the highest preference score from panelists. The longest fragrance retention was achieved by Formula 3 (15%), though its intensity was considered too strong. In conclusion, lily essential oil spray perfume can be formulated stably with adequate fragrance longevity, showing potential as a competitive natural perfume product.